2014
DOI: 10.5194/angeo-32-1455-2014
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of very low and low frequency signal variations at mid-latitudes with magnetic activity and outer-zone particles

Abstract: Abstract. The disturbances of very low and low frequency signals in the lower mid-latitude ionosphere caused by magnetic storms, proton bursts and relativistic electron fluxes are investigated on the basis of VLF-LF measurements obtained in the Far East and European networks. We have found that magnetic storm (−150 < Dst < −100 nT) influence is not strong on variations of VLF-LF signals. The anomalies with negative amplitude were registered during the main and recovery phases for several magnetic storms (mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In one case of the five, the disturbances in the signals caused by magnetic storms were not detected absolutely. These results corresponded to the conclusions that had been obtained in previous work [ 10 , 11 , 12 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In one case of the five, the disturbances in the signals caused by magnetic storms were not detected absolutely. These results corresponded to the conclusions that had been obtained in previous work [ 10 , 11 , 12 ].…”
Section: Resultssupporting
confidence: 93%
“…We can see that the magnetic storm-induced disturbances in the signals arose on the very day of the magnetic activation ( Figure 5 a), and in addition, a few days after it or after the day of the onset of magnetic activation ( Figure 5 b). Indeed, the disturbance in the signal occurred not only on the day of the magnetic storm, but also the day after it [ 10 , 11 , 12 ]. For example, if a magnetic storm began in the daytime, then as a rule, the disturbance in the signal occurred only the next day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The storm recovery phase continued for more than a week, and an intense flux of relativistic electrons was registered during that period. Although geomagnetic activity affects only the behavior of a nighttime signal on midlatitude paths (e.g., (Rozhnoi et al, 2014)) and the eclipse was observed during the daytime, this made it difficult to select quiet undisturbed days as a control for the observations. Fifteen of the 22 paths crossed the region where the occultation was 40-90%.…”
Section: Results Of Analysismentioning
confidence: 99%